Acquired atrioesophageal fistula: Need it be lethal? Sizing up the problem, diagnostic modalities, and best management. Issue 12 (20th November 2022) - Povey, Hannah G.; Page, Aravinda; Large, Stephen
Abstract: Background and Aim of the Study: An atrioesophageal fistula is a devastating complication of ablation for atrial fibrillation. For the surgeon facing this dreaded complication, it may be a 'once in a lifetime' case. This review aims to describe the clinical problem and evaluate the outcome of different surgical techniques to start guiding cardiothoracic surgeons toward those which offer the best chance of survival. Methods: An electronic search retrieved 125 articles containing 195 cases of atrioesophageal fistula secondary to atrial fibrillation ablation. Reports of pericardio‐esophageal or mediastino‐esophageal fistula were excluded. Results: The median age was 61 and 143 (73%) cases occurred in males. Fever ( n  = 147; 75%) and neurological dysfunction ( n  = 151; 77%) were the most common symptoms. The median time from ablation to symptom onset was 21 days (interquartile range: 12–28). The most sensitive thoracic imaging modality was computed tomography ( n  = 135/153; 90%). Immediate deterioration occurred during 11/58 (19%) oesophago–gastro–duodenoscopies. Mortality was lower in patients who had surgery (39%) compared with endoscopic intervention (94%) or conservative management (97%). Patients who had atrial repair combined with esophageal repair or oesophagectomy were more likely to survive than those who had atrial repair alone (OR 6.97; p  < .001). Isolation of the esophageal aspect of the fistula conferred an additional survival benefit (OR 5.85; p  = .02). Conclusions: Fever, neurological symptoms, and chest pain in the context of recent ablation should prompt immediate evaluation. Urgent CT thorax should be arranged and repeated if initially unremarkable. Esophageal instrumentation should be avoided due to the risk of catastrophic air embolism or massive hemorrhage. The best way forward is emergency surgical repair; the combination which offers the best survival benefit is atrial repair combined with esophageal surgery and isolation of the esophageal aspect of the fistula.